Analisis Pengaruh Lingkungan Belajar terhadap Prestasi Belajar Matematika Siswa di SMP Kristen Karuni - Malo, Sarmolus; Making, Samuel Rex Mulyadi; Lubur, Dorothea Novia Ludo; Lede, Yulius Keremata (Indo-MathEdu Intellectuals Journal, 2025)
This Research aims toanalyze the influece of the learning environment on the mathematics learning achievent of class VIIIA students at Karuni Christian Middle School. The learning environment in question includes physical, social, psychological aspects, as well as the learning methods applied. The research medhod used is a quantitative approach with data collection techniques through quesrionnaires and documentationnof students’ UAS scores. The research sample consisted of 27 students, research time was the even semester of the 2024/2025 academic year. Data analysis was carried out using descriptive statstics, simple linear regression tests, and pearson correlation tests eith the help of the SPSS aplication. Thr resarch results show that students’ perceptions of the learning environment are classified as good with an average score of 4.29 (scale 1-5). The average student mathematics achievement score was 74.69. the pirso correlation test shows that there is a positive and significant relationship between the learning environment anf mathematics learning schievement with a correlation coefficient (r)= 0.65 and significant (p)= 0.001. This means that the higher the mathematics learning achievement achievend.